2022
DOI: 10.2337/dc22-0073
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a Factory-Calibrated Continuous Glucose Monitor in Individuals With Diabetes on Hemodialysis

Abstract: OBJECTIVE Continuous glucose monitoring (CGM) improves diabetes management, but its reliability in individuals on hemodialysis is poorly understood and potentially affected by interstitial and intravascular volume variations. RESEARCH DESIGN AND METHODS We assessed the accuracy of a factory-calibrated CGM by using venous blood glucose measurements (vBGM) during hemodialysis sessions and self-monitoring blood glucose (SMBG) at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…rtCGM has the potential to overcome some of these challenges, but limited studies have reported the accuracy of rtCGM in people with diabetes on haemodialysis. [28][29][30] Currently, most rtCGM devices are not validated or approved for use in people on dialysis as per manufacturer's guidance because of a limited evidence base in this cohort.…”
Section: End-stage Renal Disease On Dialysismentioning
confidence: 99%
See 1 more Smart Citation
“…rtCGM has the potential to overcome some of these challenges, but limited studies have reported the accuracy of rtCGM in people with diabetes on haemodialysis. [28][29][30] Currently, most rtCGM devices are not validated or approved for use in people on dialysis as per manufacturer's guidance because of a limited evidence base in this cohort.…”
Section: End-stage Renal Disease On Dialysismentioning
confidence: 99%
“…Overall assessment of glycaemia in end‐stage renal disease is difficult as classical markers such as HbA1c may underestimate glycaemia because of a shortened erythrocyte lifespan and does not differentiate glycaemia on the days on and off dialysis. rtCGM has the potential to overcome some of these challenges, but limited studies have reported the accuracy of rtCGM in people with diabetes on haemodialysis 28–30 . Currently, most rtCGM devices are not validated or approved for use in people on dialysis as per manufacturer's guidance because of a limited evidence base in this cohort.…”
Section: Real‐time Continuous Glucose Monitoring Technologymentioning
confidence: 99%
“…These studies have demonstrated the ability to identify CGM patterns in patients on hemodialysis (72,73) and assess the reliability of current measurement methodologies (74,76,77). Indeed, a recent study of patients with diabetes receiving hemodialysis reported reasonable accuracy and clinical utility of the factory-calibrated Dexcom G6 Pro CGM, concluding that use of the device holds promise for assessment of glycemic control and informing clinical management decisions (78). Recently, two pilot clinical trials evaluated the safety and efficacy of a closed-loop system (CamAPS HX Close Loop; CamDiab), including a Dexcom G6 CGM and the Dana Diabcare RS insulin pump, among patients treated with hemodialysis.…”
Section: Use Of Continuous Glucose Monitoring In Managing Glycemiamentioning
confidence: 99%
“…The latest Kidney Disease Improving Global Outcomes (KDIGO) guideline advocates the use of periodic continuous glucose monitoring (CGM) alongside HbA 1c in stage 4 to 5 chronic kidney disease ( 5 ). Recently published studies focused on the evaluation of accuracy of CGM in HD patients ( 6 8 ). However, few studies have been conducted in PD patients ( 9 , 10 ), mostly using self-monitoring of blood glucose (SMBG) as the comparator within a limited glycemic range.…”
Section: Introductionmentioning
confidence: 99%